DEVELOPMENT OF VIRTUAL REALITY-BASED UNIFIED MODELING LANGUAGE GAMIFICATION SOFTWARE (CASE STUDY: CLASS DIAGRAM) - Fadil, Amar
The main stage in software development is software modeling, one of which uses Unified Modeling Language (UML) diagrams. UML diagrams are quite popular, even adopted by many universities for software modeling. However, traditional learning methods are considered boring and less engaging. One way to make learning more enjoyable is gamification, which involves using game elements in non-game contexts, based on virtual reality (VR). VR allows for immersive experiences and supports social interaction among players. This thesis aims to develop VR-based UML diagram modeling gamification software by considering social aspects, making UML modeling exercises easy to use as well as interesting/enjoyable. This solution is developed using the ADDIE method in three systems: the gamification system, the game system, and the networking system. This thesis implements the gamification system and the game system, while the networking system uses Photon Cloud Server. The gamification system is implemented as a backend to store gamification states, developed using Flask. The game system is developed with Unity, Mixed Reality Toolkit, and Photon Fusion to support VR interaction and network synchronization. The alternative solutions developed include three game types: single-player, collaborative multiplayer, and competitive multiplayer. In the single-player and collaborative multiplayer game types, there are two types of score gamification: points and time. The results of this software development will be tested functionally to ensure the software's quality. The software was tested with users to determine the ease of use and enjoyment of the developed solution. From the test results, it was found that all game types and gamification score type are quite easy to use with a SUS score above 68. Additionally, all solutions have an average Interest/Enjoyment subscale using the Intrinsic Motivation Inventory that is quite high, which is above 5.9 on a 7-point Likert scale. These results show that the developed VR gamification software is not only easy to use but also engaging/enjoyable for users.